Multimodality imaging‐guided local injection of eccentric magnetic microcapsules with electromagnetically controlled drug release. Issue 2 (21st December 2018) - Huang, Wenwei; Chen, Yin; Chen, Lanxi; Zhong, Jinshuang; Johri, Amer M.; Zhou, Jianhua
Abstract: Background: In the past decade, trackable smart drug delivery systems have played important roles in the treatment of many diseases such as cancer because the drug carriers can be visualized through their distinct physical properties. However, it is still difficult to achieve precise drug delivery because such systems usually rely on a single imaging system. Aim: This study aimed to present a novel type of multimodality imaging‐guided strategy to visualize the drug carriers of eccentric magnetic microcapsule (EMM) designed for potential treatment of hepatocellular carcinoma (HCC). Method and results: The EMMs were prepared by using a three‐phase microfluidic device. The as‐prepared EMMs embedded with Fe3 O4 nanoparticles are magnetic, with high density and acoustic impedance, allowing for visualization by magnetic resonance imaging (MRI), computed tomography (CT), and ultrasound (US) imaging during local injection. The release of drug from these EMMs can be further controlled by an external electromagnetic field (EMF). As a proof of concept, we demonstrated the process of multimodality imaging to guide local injection and the controlled release of doxorubicin (DOX) from the EMMs in a phantom. We showed that the release rate of DOX was directly correlated to the strength of the EMF. In addition, we cocultured green fluorescent protein (GFP)‐transfected HeLa cancer cells with the DOX‐loaded EMMs and documented their apoptosis by DOX following the release triggered by EMF. Conclusion: The results suggest that these EMMs serve both as contrast agents that can be visualized by multimodality imaging techniques and as smart drug delivery systems, with great potential for precision medicine.